Seasonally stable temperature gradients through supraglacial debris in the Everest region of Nepal, Central Himalaya - Ann V. Rowan; Lindsey I. Nicholson; Duncan J. Quincey; Morgan J. Gibson; Tristram D.L. Irvine-Fynn; C. Scott Watson; Patrick Wagnon; David R. Rounce; Sarah S. Thompson; Philip R. Porter; Neil F. Glasser (Journal of Glaciology, 2021)
Rock debris covers ~30% of glacier ablation areas in the Central Himalaya and modifies the impact of atmospheric conditions on mass balance. The thermal properties of supraglacial debris are diurnally variable but remain poorly constrained for monsoon-influenced glaciers over the timescale of the ablation season. We measured vertical debris profile temperatures at 12 sites on four glaciers in the Everest region with debris thickness ranging from 0.08 to 2.8 m. Typically, the length of the ice ablation season beneath supraglacial debris was 160 days (15 May to 22 October)—a month longer than the monsoon season. Debris temperature gradients were approximately linear (r2 > 0.83), measured as −40°C m–1 where debris was up to 0.1 m thick, −20°C m–1 for debris 0.1–0.5 m thick, and −4°C m–1 for debris greater than 0.5 m thick. Our results demonstrate that the influence of supraglacial debris on the temperature of the underlying ice surface, and therefore melt, is stable at a seasonal timescale and can be estimated from near-surface temperature. These results have the potential to greatly improve the representation of ablation in calculations of debris-covered glacier mass balance and projections of their response to climate change.